Research progress of aqueous Zn–CO2 battery: design principle and development strategy of a multifunctional catalyst - Guo, Wenqi; Wang, Yukun; Yi, Qun; Devid, Edwin; Li, Xuelian; Lei, Puying; Shan, Wenlan; Qi, Kai; Shi, Lijuan; Gao, Lili (Frontiers in Energy Research, 2023)
Aqueous Zn-CO2 battery possesses a large theoretical capacity of 820 mAh g-1 (5855 mAh cm-3) and high safety, showing a unique position in carbon neutrality and/or reduction and energy conversion & storage, which has developed rapidly in the recent years. However, the obstacles such as low value-added products, low current density, high overvoltage and finite cycles impede its practical application. Cathode catalyst, as a key component, has a great influence on gas cell performance. Despite many updated papers on cathode materials for aqueous Zn-CO2 battery, a systematic summary has rarely been reported, and even less is mentioned about the design principle and development strategy for efficient catalysts. Relying on the structure and mechanism of Zn-CO2 battery, in this review is discussed the research progress, existing challenges and more importantly the design strategies and preparation methods of the efficient cathode are proposed, centering on: materials structure, charge distribution, and coordination environment. Finally, in this review is highlighted the opportunities for the development of a high-performance Zn-CO2 battery, which enable to enlighten the future exploration of next-generation energy storage systems.